Impacts of COVID-19 pandemic on Jiu-Jitsu practitioners in Brazil (Research, Society and Development, 2022)
Objective: to analyze the impacts of COVID-19 pandemic on routine of Brazilian Jiu-Jitsu practitioners in Brazil. Methodology: this is a quantitative, descriptive, exploratory and transversal study with survey. The research was carried out with Brazilian Jiu-Jitsu practitioners during the COVID-19 pandemic, through a self-administered online questionary and COVID-19 Fear Scale. A statistical analysis was performed using chi-square tests and analysis of variance. Results: the study involved 204 participants with average age of 29±8.81 years. Among the impacts generated by the COVID-19 pandemic on the routine of these practitioners, the following stand out: reduction of training hours (p < 0.0001), weekly training frequency (p < 0.0001) and weekly classes taught by teachers of the modality (p < 0.0001). In addition, negative effects on performance of participants diagnosed with COVID-19 (n=68) were evidenced, such as difficulty breathing (22.1%), anxiety (20.6%) and muscle weakness (19.1%). This diagnosis required absence from training, on average, for 31.75±16.50 days. Conclusion: the COVID-19 pandemic impacted the routine of Brazilian Jiu-Jitsu practitioners, which may have negatively affected the short and long-term sports performance of these individuals